EKOLOGI BUDAYA DAN NILAI KEARIFAN LOKAL POHON SAGU DALAM DIMENSI MASYARAKAT SUKU TOLAKI - Sabaruddin Sinapoy; Basrin Melamba; Herman Herman (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2021)
Sinapoy, S., Melamba, B., & Herman. (2021). Ekologi budaya dan nilai kearifan lokal pohon sagu dalam dimensi masyarakat suku Tolaki. ETNOREFLIKA: Jurnal Sosial Dan Budaya, 10(3), 323–342. https://doi.org/10.33772/etnoreflika.v10i3.1163 ABSTRACT Sago, as the identity of the indigenous people of the Tolaki tribe, besides having many values ​​and benefits also contains historical and philosophical values, so that the position of sago is very important to the life of the Tolaki ethnicity in Southeast Sulawesi. Philosophical values ​​contained in sago plants/trees are the values ​​of local wisdom related to its relationship with culture and the environment called cultural ecology. Local wisdom in cultural ecology for the indigenous people of the Tolaki tribe is always interconnected to the "kalosara" philosophy. Thus, the value of lakol sago wisdom in cultural ecology can be seen from the implementation of the "kalosara" philosophy itself. The survivability of the Tolaki people and their culture to date in the management and utilization of sago plants/trees is very likely due to this universal nature. Thus, the cultural ecology of the local community through its local wisdom regulates the pattern of community behavior. Community behavior patterns based on local wisdom tend to be more ecological than modern societies that do not use local wisdom in their lives. Local wisdom acts not only as a controller of individual human life, but it should also have thought of the survival of other humans in the area and also the sustainability of the surrounding natural environment as one of sustainable development goals.